Effectiveness of the Kundalini Method in Reducing Emesis Gravidarum in the 1st Trimester - Khusmitha, Qatrunnada Naqiyyah; Farokah, Atik; Putri, Herdian Fitria Widyanto (Universitas Aisyah Pringsewu, 2023)
Stunting is a common occurrence, and one of the causes is pregnant women's nutritional state. The mother experiences nausea, vomiting, and a lack of appetite in the first trimester of pregnancy as a result of physiological changes, including an increase in hCG and modifications to glucose metabolism. One activity with a history of success in lowering anxiety problems is Kundalini Yoga. The design of this study is quasi-experimental with sampling techniques using total sampling. All 1st-trimester pregnant women in the Mancon Polindes work area were measured for nausea and vomiting using the PUQE-24 questionnaire. Kundalini yoga is given by researchers who have been supervised by certified yoga instructors. For individual training at home, pregnant women are given videos as a guide. Assessment will be carried out within 1 month. Data were analyzed using descriptive and inferential statistics (t-test). The amount of nausea experienced by pregnant women in their first trimester differed significantly between the treatment group and the control group (p = 0.000, p0.05). Vomiting rates in the treatment group and the control group were significantly different after the Kundalini technique therapy (p = 0.000, p0.05). Kundalini yoga is an effective strategy for reducing emesis gravidarum in pregnancy.